Influência do grau de desidroxilação na reatividade de argilas cauliníticas calcinadas - Pires, Maikon Moreira de (Universidade do Vale do Rio dos Sinos, 2023)
The high consumption of Portland cement worldwide brings with it the responsibility for its environmental impacts due to its high carbon dioxide (CO2) emissions originating from the clinker manufacturing process. Thus, a strategy adopted to reduce CO2 emissions is the partial replacement of clinker with supplementary cementitious materials (SCMs). Among the SCMs are calcined clays, especially kaolinitic clays. In order for clays to become active, meaning that silicon and aluminum are available to react with calcium hydroxide and carbonates in the case of LC3 cement, they need to be activated, which occurs through temperatures above 500°C. Kaolinite is one of the main clay minerals that compose kaolin, with a chemical composition of Al2Si2O5(OH)4, being a 1:1 dioctahedral phyllosilicate structure. Dehydroxylation consists of the removal of this hydroxyl, disrupting the crystalline structure and making silica and alumina available for pozzolanic reactions. This research aimed to evaluate the influence of dehydroxylation degree on the reactivity of kaolinitic clays. For this purpose, two kaolinitic clays called white kaolin and pink kaolin were used, with a total sum of ∑SiO2;Al2O3;Fe2O3 of 79% and 77%, respectively, and a sum of ∑SiO2;Al2O3 of 78% for the white clay and 76% for the pink clay. Calcination temperatures of 550, 650, 750, and 850°C were used, with residence times of 15 and 45 minutes. The degree of dehydroxylation was correlated with the physical and chemical characteristics of the clays, as well as with the consumption of Portlandite (CH), combined water, and compressive strength of cement pastes. After analyzing the results, it was possible to infer that although the degree of dehydroxylation positively influenced the consumption of CH and the content of combined water, the most influential factor in the development of reactivity of the evaluated clays was the specific surface area. As the chemical parameters of the clays were similar, as well as particle size, arrangement of hydroxyls, and surface regularity, the higher reactivity of the pink kaolinitic clay can be attributed to its higher specific surface area (twice the SS of the white clay).
Keywords: Cimento Portland; Argilas cauliníticas calcinadas; Grau de desidroxilação; Reatividade; Área superficial específica; Portland cement; Calcined kaolinitic clays; Dehydroxylation degree; Reactivity; Specific surface area; ACCNPQ::Engenharias::Engenharia Civil